Post-treatment testicular activity in lymphoma patients - Ahmad, Mushtaq; Lone, Abdul Rashid; Kuchai, Sana Ullah; Zargar, Abdul Hamid; Aziz, Sheikh Aejaz; Bhat, Gul Mohammad; Banday, Manzoor A; Jelani, Samoon; Bhat, Javid Rasool (Indian Journal of Medical and Paediatric Oncology, 2008)
Objectives: For young patients receiving cancer chemotherapy, the major concern is gonadal dysfunction with impaired reproductive capacity. The impact of such therapy in patients with lymphoma was focus of this study. Methods : Semen analysis and serum FSH and LH levels were determined pretreatment, immediately after completion of therapy and at follow-up in 60 patients of lymphoma receiving chemotherapy. Results : Pretreatment infertility was present in 13.2% of patients. After completion of treatment, 76.9% developed azoospermia. However, after a mean follow up of 56.66 months, percentage of normospermic patients declined to 43.3%, recovery being better in patients of age less than 30 years. Conclusion : The effects of chemotherapy on testicular activity were significant with combination containing cyclophosphamide and procarbazine. Recovery in spermatogenesis and FSH levels to normal was seen in patients receiving cyclophosphamide, vincristine and prednisolone but was least when procarbazine was added to this. 90% patients continued to have azoospermia at 5 years in the group which received cyclophosphamide in combination with procarbazine.